A C(sp2)−H Dehydrogenation of Heteroarenes and Arenes by a Functionalized Aluminum Hydride. Issue 55 (7th September 2017) - Chen, Shimin; Li, Bin; Wang, Xiaoping; Huang, Yanting; Li, Jiancheng; Zhu, Hongping; Zhao, Lili; Frenking, Gernot; Roesky, Herbert W.
Abstract: The 2‐aminophenylaluminum dihydride (2‐TMP‐C6 H4 )AlH2 (2 ) has been prepared and characterized for the first time. Compound 2 features an intramolecular N⋅⋅⋅Al donor–acceptor bond.2 reacted with N ‐methylpyrrole and N ‐methylindole (both at 50 °C) by means of the elusive AlH C(sp 2 )−H dehydroalumination to aluminum heteroaryls (3 and4 ). Moreover, 2 reacted with PhCCSiMe3 (at room temperature) and Ph2 CCNR (R= i Pr or 2, 6‐ i Pr2 C6 H3, at −30 to 20 °C ) to yield aluminaindene heterocycle (8 ) and alumina‐aza‐naphthalene heterocycle (9 and10 ), respectively. These reactions underwent hydroalumination followed by AlH C(sp 2 )−H dehydroalumination. The reaction mechanism has been studied by combining experiment and quantum chemical calculations, with the result that the key heteroarene or arene C(sp 2 )−H bond activation is involved under cooperative interaction by the inherent N/Al donor/acceptor pair. The reported reactions open a straightforward route to heteroaryl and unique heterocyclic aluminum compounds. Abstract : A functionalized aluminum hydride (2‐TMP‐C6 H4 )AlH2 has been prepared. The inherent N/Al donor/acceptor pair cooperatively activates the C(sp 2 )−H bond, which improves the aluminum hydride reactivity by the elusive C(sp 2 )−H dehydroalumination of N ‐heteroarenes and multiple‐bond‐containing arenes. These reactions open a straightforward route to heteroaryl and unique heterocyclic aluminum compounds.